The characterization of the basidiomycetes and other fungi associated with esca of grapevines in South Africa - White, Chana-Lee (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Plant Pathology))--University of Stellenbosch, 2010.